eGovernment Integration Framework for Fragmented Systems - Paradkar, Sameer S (International Journal of Computer Sciences and Engineering, 2021)
This paper proposes an integration framework for the Public Institutions / government entities wishing to integration fragmented applications and systems. The existing alternatives of integration falls short of attributes like performance, interoperability, and reliability. This paper proposed a Microservices Based Integration and API driven approach that will achieve the resiliance and scale. We propose a model based on API and microservices framework leveraging API Gateway, API Management, ESB, Orchestrator, and Rules engine. This paper intends to provide a comprehensive list of integration capabilities based on the underlying integration framework. This framework is an enabler to digitally transform in government enterprise and to provide sufficient impetus and acceleration for its digital future.